Transnational Partisanship and Networked Constituent Power in the EU - Fabio Wolkenstein (London School of Economics and Political Science (LSE), European Institute, 2018)
The constitutional politics of the European Union have been intensely debated in recent times. A key concern, voiced both within the academy and at street level, is how citizens could be endowed with the ability to shape, revise and legitimise evolving constitutional settlements. This paper begins by discussing recent accounts of 'constituent power' in the EU that seek to offer guidance in this respect. It argues that these accounts are normatively insightful but ultimately stop short of providing a viable model of constitutional agency. The remainder of the paper then aims to examine what such a model could look like, looking for inspiration to the muchneglected political practice of transnational partisanship. Specifically, the paper examines the transnationally coordinated constitution-making efforts of Christian Democratic partisans in the founding period of the EU, suggesting that there is much to learn from these efforts as far as EU constitutional politics is concerned.
Keywords: 330; Transnational partisanship; constituent power; EU constitutionalism; Christian Democracy; Jürgen Habermas